WEBSITE PROMOSI UNTUK INTENSIVE EDU - Arisandi, Desi; Tony; Pranata, Edward Brainard (Jurnal Serina Abdimas, 2023)
Intensive Edu is a non formal education institution located in Modernhill, Pondok Cabe, South Tangerang. Intensive Edu provides private courses or lessons, especially Cambridge Lessons and Mandarin for elementary/junior high school students. Currently, Intensive Edu is promoting through social media Instagram and Whatsapp, as well as word of mouth. With the increasing number of students taking tutoring at Intensive Edu, the need for digital promotions is urgently needed. One of the media that will be used for promotion is using a website. Intensive Edu hopes to have a website that will be used to promote the tutoring program offered and attract more students. Therefore, the community service implementation team (PKM) consisting of lecturers and students from the Tarumanagara University Information Systems Study Program and Computer Science, offered to design and create a website for Intensive Edu. Website prototype is developed using WordPress website builder which supports HTML (HyperText Markup Language), PHP (Hypertext Preprocessor), CSS (Cascading Style Sheets), and MySQL as a database. The website for Intensive Edu is hosted on the Internet at https://intensive-edu.com/. Intensive Edu merupakan lembaga pendidikan yang berlokasi di Perumahan Modernhill, Pondok Cabe, Tangerang Selatan. Intensive Edu memberikan kursus atau les privat, terutama Cambridge Lesson dan bahasa Mandarin untuk siswa-siswi SD/SMP. Saat ini, Intensive Edu melakukan promosi melalui media sosial Instagram dan Whatsapp, serta mulut ke mulut (word of mouth). Dengan semakin bertambahnya jumlah siswa yang les di Intensive Edu, kebutuhan untuk melakukan promosi secara digital sangat diperlukan. Salah satu media yang akan digunakan untuk melakukan promosi adalah menggunakan website. Intensive Edu berharap dapat mempunyai sebuah website yang akan digunakan untuk melakukan promosi program les yang ditawarkan dan menjaring jumlah siswa lebih banyak. Oleh karena itu, tim pelaksana kegiatan pengabdian kepada masyarakat (PKM) yang terdiri dari dosen dan mahasiswa dari Program Studi Sistem Informasi dan Informatika Universitas Tarumanagara menawarkan perancangan dan pembuatan website untuk Intensive Edu. Prototipe website dibuat dengan menggunakan website builder Wordpress yang mendukung bahasa pemrograman HTML (HyperText Markup Language), PHP (Hypertext Preprocessor), CSS (Cascading Style Sheets), dan MySQL sebagai basis data. Website untuk Intensive Edu sudah di-hosting di Internet dengan alamat https://intensive-edu.com/.